High-Precision Ion Beam Figuring of X-Ray Plane Mirrors for the Bendable KB Focusing System - Zhang, Yunyang; Huang, Qiushi; Yan, Shuai; Yu, Jun; Huang, Handan; He, Yumei; Luo, Hongxin; Liu, Zhi; Zhang, Zhong; Wang, Zhanshan (Frontiers in Physics, 2022)
Two trapezoidal plane mirrors of 240 mm in length were fabricated by ion beam figuring (IBF) technology for application in a bendable KB focusing system. The correction of surface height and slope errors in different spatial frequency ranges of the mirrors was studied systematically. After one to two iterations of IBF, the figure height errors of the vertical focusing mirror (VFM) and horizontal focusing mirror (HFM) were improved from 32.4 and 65.4 nm to 2.7 and 7.2 nm (RMS), respectively. If the best-fit sphere of the surface profile was subtracted, the residual two-dimensional height errors were only 1.1 and 1.2 nm (RMS). The slope errors in the low spatial frequency range were corrected much faster than the middle frequency ones (f = ∼1 mm−1), which make the low-frequency slope error much smaller. After IBF, the two-dimensional slope errors of the two mirrors calculated with a spatial interval of 1 and 10 mm were reduced to approximately 0.29 and 0.08 μrad, respectively. Full spatial frequency characterization of the VFM before and after IBF showed that the low-frequency figure errors (f < 1 mm−1) were significantly reduced while the middle- and high-frequency morphologies (f > 1–2 mm−1) remain almost the same as before figuring. The fabricated plane mirrors were applied in the hard X-ray micro-focusing beamline in the Shanghai Synchrotron Radiation Facility (SSRF), which realized a focal spot of 2.4 μm × 2.8 μm at 10 keV.